ASSESSING THE RELATIONSHIP BETWEEN TRANSFORMATIONAL LEADERSHIP AND EMPLOYEE PERFORMANCE IN THE HEALTH DEPARTMENT OF EAST JAKARTA - Syahrir; Hasan, Diana Sukmawati (PROCURATIO: Jurnal Manajemen & Bisnis, 2023)
This research focuses on exploration of the impact of transformational leadership on employee performance, with the aim of gaining a deeper understanding of this relationship. The hypothesis tested in this study states that transformational leadership style has a significant influence on employee performance. leadership style has a significant influence on employee performance. In collecting data, This study involved 156 respondents as a representative sample of the population. The data analysis method used is inferential analysis, allowing the researchers to draw broader conclusions from this limited sample. The results of the study revealed that there is a positive and significant influence between transformational and employee performance. This means that a leadership style that focuses on developing individual potential, motivating, and creating a shared vision have a real impact on employee performance. a real impact on employee performance. The conclusion of this study contributes to our understanding of the importance of transformational leadership in the context of work environment. The practical implications of this research can serve as a basis for organizations to develop and improve their leadership practices to improve overall employee performance.